Colonial Boundaries: The Philippine Territories During the Spanish Era (British Journal of Multidisciplinary and Advanced Studies, 2026)
Spanish colonization of the Philippines from 1521 to 1898 brought profound transformations in society, politics, and the economy. From the arrival of Ferdinand Magellan to the consolidation of hundreds of islands into Las Islas Filipinas, the Spanish established territorial control that defined the archipelago as a unified colony. Central to this was the 1734 Murillo Velarde map, which provided the first precise delineation of the Philippine territory. This study examines how Spanish colonial authority shaped, expanded, and maintained these territorial domains, as well as the challenges and resistance encountered across the islands. Drawing from primary sources, it explores five key questions: the strategies used by the Spaniards to overcome resistance; the territories brought under colonial control; the barriers to maintaining authority; the territorial changes across three centuries; and the broader impact of colonial expansion. By analyzing these aspects, the study highlights the Philippines’ significance as a vital colony of the Spanish Empire and underscores the lasting legacy of Spanish territorial hegemony.